The effects of S-nitrosoglutathione and S-nitroso-N-acetyl-D, L-penicillamine in a rat model of pre-eclampsia - Brown, Caneta (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Pre-eclampsia (PE) complicates approximately 5-7% of all pregnancies. This study investigates the effects of S-nitroso-N-acetylpenicillamine (SNAP) and S-nitrosoglutathione (GSNO) on the classical features of PE. MATERIALS AND METHODS: On day 14 of gestation, female Sprague-Dawley rats were separated into five groups and treated intravenously for 7 days as follows: (i) 0.3 mL 0.9% saline (control, n = 11); (ii) 50 mg/kg Body Weight (BW) N-nitro-L-arginine methyl ester (L-NAME) in 0.3 mL saline (n = 10); (iii) 50 mg/kg BW L-NAME and 8 mg/kg BW GSNO in 0.15 mL saline (n = 6); (iv) 50 mg/kg BW L-NAME in 0.15 mL saline and 8 mg/kg BW SNAP in 0.15 mL DMSO (n = 9); and (v) 0.15 mL DMSO and 0.15 mL saline (SNAP control, n = 7). Blood pressures were measured on day 14 through day 20, a 4-h urine sample was taken on day 20, and animals were sacrificed on day 21. Pups were counted and weighed individually. RESULTS: SNAP and GSNO significantly decreased systolic, diastolic, and mean arterial pressures in PE-induced rats from day 14 through day 20 (P < 0.05). Pup weights in SNAP and GSNO groups were higher than in L-NAME group but lower than in controls (P ≤ 0.001). SNAP and GSNO partially reversed growth retardation. CONCLUSION: Elevated blood pressure, proteinuria, and intrauterine growth restriction associated with PE were induced in Sprague-Dawley rats using L-NAME. These were partially reversed with the use of GSNO and SNAP. The mechanism of action of these S-nitrosothiols (RSNOs) should be further explored.